2011
DOI: 10.1371/journal.pone.0016953
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotic Sonicates Selectively Induce Mucosal Immune Cells Apoptosis through Ceramide Generation via Neutral Sphingomyelinase

Abstract: BackgroundProbiotics appear to be beneficial in inflammatory bowel disease, but their mechanism of action is incompletely understood. We investigated whether probiotic-derived sphingomyelinase mediates this beneficial effect.Methodology/Principal FindingsNeutral sphingomyelinase (NSMase) activity was measured in sonicates of the probiotic L. brevis (LB) and S. thermophilus (ST) and the non-probiotic E. coli (EC) and E. faecalis (EF). Lamina propria mononuclear cells (LPMC) were obtained from patients with Croh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
(53 reference statements)
0
18
0
Order By: Relevance
“…Although several mammalian SMases have been characterized, neutral sphingomyelinase 2 (NSMase 2, SMPD3) and acid sphingomyelinase (ASMase, SMPD1) are the most extensively studied enzymes in ceramide generation, and the most relevant in cell death Morales et al, ACA-MC 8 regulation and pathology. While NSMase-induced ceramide generation has been described as a critical lipid in inflammatory diseases and oocyte maturation [29,30], ASMase with an optimum pH of 4.5-5.5, has been extensively described as a signaling intermediate in cell death pathways, of particular relevance in the progression of liver diseases [24,27,28,31]. ASMase catalyzes the formation of ceramide from SM primarily within the endo-lysosomal compartment, although it can be secreted extracellularly through Golgi trafficking as a secretory ASMase (S-SMase) [3,4].…”
Section: Ceramide Generation Through Hydrolysis Of Higher Sphingolipidsmentioning
confidence: 99%
“…Although several mammalian SMases have been characterized, neutral sphingomyelinase 2 (NSMase 2, SMPD3) and acid sphingomyelinase (ASMase, SMPD1) are the most extensively studied enzymes in ceramide generation, and the most relevant in cell death Morales et al, ACA-MC 8 regulation and pathology. While NSMase-induced ceramide generation has been described as a critical lipid in inflammatory diseases and oocyte maturation [29,30], ASMase with an optimum pH of 4.5-5.5, has been extensively described as a signaling intermediate in cell death pathways, of particular relevance in the progression of liver diseases [24,27,28,31]. ASMase catalyzes the formation of ceramide from SM primarily within the endo-lysosomal compartment, although it can be secreted extracellularly through Golgi trafficking as a secretory ASMase (S-SMase) [3,4].…”
Section: Ceramide Generation Through Hydrolysis Of Higher Sphingolipidsmentioning
confidence: 99%
“…In addition to de novo synthesis in the ER, ceramide can be generated by sphingomyelin (SM) hydrolysis by sphingomyelinases (SMases) [14]. Although, the neutral SMase (NSMase) has been shown to induce apoptosis [15, 16], this outcome may be dependent on the topology/sidedness of NSMase-induced ceramide generation [17]. Moreover, acid SMase (ASMase) mediates apoptosis in response to cell death receptors, chemotherapy or ionizing radiation [18–20].…”
Section: Introductionmentioning
confidence: 99%
“…Neutral sphingomyelinase (NSMase) and acid sphingomyelinase (ASMase) are the most studied enzymes in ceramide generation, which have been involved in pathophysiological processes and disease. In this regard, NSMase-induced ceramide generation has been described as a critical lipid mediator in inflammatory diseases and X. laevis oocyte maturation [28, 29]. Moreover, ASMase has been characterized as a signaling intermediate in extrinsic cell death pathways and liver diseases [30-36].…”
Section: Gsls Generation Metabolism and Role In Cell Deathmentioning
confidence: 99%
“…Recent evidence has shown that NSMase cooperates with Bak and Bax to promote the mitochondrial pathway of apoptosis [49]. In addition, bacterial NSMase has been identified as a key component of the therapeutic effects of the probiotic formulation VSL#3 in inflammatory bowel disease due to the selective induction of apoptosis of activated mucosal immune cells, as the beneficial effects of VSL#3 were prevented by NSMase inhibition with GW48469 [28]. …”
Section: Gsls Generation Metabolism and Role In Cell Deathmentioning
confidence: 99%